140 Perfectly balanced, as all things should be: rota management in the era of flexible training. (17th August 2022) - Watkin, David
Abstract : Aims: Health Education England (HEE) established the 'Enhancing Junior Doctors' Lives' programme in 2016, aiming to address a range of issues that were having a significant negative impact on the quality of life of doctors in training. As part of the programme, paediatric trainees became eligible for Category 3 less-than-full-time (LTFT) working; that is, LTFT as a personal choice that meets their individual professional or lifestyle needs. Whilst the potential benefits to the LTFT trainee are numerous, and the hypothesised improvement in trainee recruitment and retention may benefit the health service overall, LTFT working can provide challenges to those managing rotas. These challenges include the provision of an even staffing level throughout the week, and ensuring that all trainees have equitable access to learning opportunities. As a quality-improvement project, we aimed to develop a method of co-ordinating trainee work patterns, to provide consistent staffing levels within the Tier 2 (ST4-8) rota of a General Paediatric team based at a tertiary children's hospital. The General Paediatrics registrars cover inpatients, new admissions, primary care and ED referrals, HDU, specialty consults and safeguarding. The roster consists of paediatric ST4-8 trainees, as well as non-rotating Clinical Fellows. A minimum of three Tier 2 doctors are required to safely staff the department. Methods: Previously, individuals chose their 'off' days independently, with the rota then being constructed within those parameters. Unsurprisingly, some days were more popular than others as 'off' days, with too few staff on Mondays and an excess of staff during midweek. The rota management team (1x paediatric consultant and 1x Clinical Fellow) decided to use a planned rotation of trainees to try to balance the rota, aiming for even staffing throughout the week. Of the new rotation, 71% of individuals worked LTFT, with a median of 0.8 FTE. We initially modelled a rota based on the Clinical Fellows only (as those who worked LTFT had contractually-fixed work-patterns). After this, we contacted all of the new trainees to ascertain a) their work-pattern, b) their preferred 'off' days and alternatives, and c) their degree of flexibility. These were then mapped onto the new rota; if there was uneven staffing, those with greater flexibility were offered their first-alternative 'off' days. Results: When taking trainees' first choices into account only, there was marked variation in staffing throughout the week, ranging from four doctors on a Monday to nine doctors on a Tuesday and Friday. When using a system of 'first alternatives', the amount of variation was greatly reduced; with a range of six doctors on a Monday to nine doctors on a Tuesday ( table 1 ). Conclusion: Flexible training has multiple benefits for both trainees and for the health service. LTFT training is common in paediatrics and is likely to become even more so; departments should consider whether planning service and training around a 'default' full-time trainee is still appropriate in this new era. Whilst LTFT working can pose challenges for service-planning, it is by taking pro-active steps that departments can provide the best service for patients and best learning environment for trainees.